Interactive E learning environment for mixer in RF IC - Nur Hidayah Ishak (2019)
This Final Year Report presents the overall implementation on Interactive E Learning Environment for Mixer In RF IC where it is being implemented based on a web design. This report starts with an introduction of E learning education followed by the objectives and scope of this project. This report provides background on the E-Learning topic of Mixer in RF IC and the application as well. It also includes the process of implementing the Website platform using different kinds of software tools and the testing. Visual aid like video is being provided. After which, open ended questions banks are being implemented for users to access their understanding of the topic. There are guided solutions provided for them. Simulation in the Matlab were also used to assist in the student’s learning. Lastly, the report includes the future works and how this Learning Environment creates a conducive platform to engage students in learning.